Improved cyclic retention and high‐performance supercapacitive behavior of poly(diphenylamine‐co‐aniline)/phosphotungstic acid nanohybrid electrode. (1st August 2020) - Eswaran, Muthusankar; Wabaidur, Saikh Mohammad; Alothman, Zeid Abdullah; Dhanusuraman, Ragupathy; Ponnusamy, Vinoth Kumar
Summary: In this study, a simple and facile electrochemical deposition technique was employed to fabricate fluorine‐doped tin oxide‐based polydiphenylamine‐polyaniline/phosphotungstic acid copolymer nanocomposite modified electrode (FTO/PDPA‐PANI/PTA) for high‐performance supercapacitors application. Crystalline and morphological structure and coating thickness of PDPA‐PANI/PTA nanocomposite on FTO were characterized using X‐ray diffraction, scanning electron microscope, and atomic force microscope. The fabricated nanohybrid electrode exhibits superior specific capacitance of 360 Fg −1 at 1 mA current density. The higher capacitive behavior and cyclic steadiness of FTO/PDPA‐PANI/PTA modified electrode were achieved because of the presence of tungsten in the PDPA/PANI co‐polymer nanonetworks provide efficient interaction which enhances the fast electron transfer progressions. Electrochemical impedance spectroscopic (EIS) studies ensure the capacitive behavior of the electrodeposited nanohybrid modified electrode with a characteristic EIS semicircle in the lower frequency region. Further, a superior specific capacitance with 82% excellent capacitance retention after 1000 cycles, recommends a practical application in supercapacitor device electrodes. Abstract : Polydiphenylamine/polyaniline/phosphotungstic acid copolymer nanohybrid modified FTO electrode for higher capacitive behavior and cyclic steadiness.